2015
DOI: 10.1016/j.neures.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Phase coherence of auditory steady-state response reflects the amount of cognitive workload in a modified N-back task

Abstract: The auditory steady-state response (ASSR) is an oscillatory brain activity evoked by repetitive auditory stimuli. Previous studies have reported that the power and phase locking index (PLI) of ASSR could be modulated by the degree of workload. However, those studies used different physical stimuli for tasks of differing difficulty, and the effect of the internal workload itself has not been clearly understood. In this study, we employed the modified N-back task as a visual working memory task in order to vary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…The PLI of the ASSR measured by the wearable EEG system significantly decreased as the task difficulty increased. This result is consistent with our previous MEG study (Yokota and Naruse, 2015). Moreover, the PLI was modulated not only according to task difficulty but also the block (experimental order).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The PLI of the ASSR measured by the wearable EEG system significantly decreased as the task difficulty increased. This result is consistent with our previous MEG study (Yokota and Naruse, 2015). Moreover, the PLI was modulated not only according to task difficulty but also the block (experimental order).…”
Section: Discussionsupporting
confidence: 94%
“…They suggested that the workload related with visual modality has induced desynchronization of 40 Hz ASSR. Previously, we observed a change in the ASSR associated with cognitive load (Yokota and Naruse, 2015). Thus, it appears that the ASSR can be modulated by workload changes in several modalities.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations